The Difference of Intraocular Pressure between Schiotz Tonometer and Non Contact Tonometer in Surakarta - Rizky Hanifah Nadiawati; Kurnia Rosyida .; Lukman Aryoseto . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Rizky Hanifah Nadiawati, G0012192, 2015. The Difference of Intraocular Pressure between Schiotz Tonometer and Non Contact Tonometer in Surakarta. Mini Thesis. Faculty of Medicine, Sebelas Maret University, Surakarta. Introduction: Intraocular pressure (IOP) is the pressure inside the eyeball measured by tonometer. There is a lot kinds of tonometer, two of them are schiotz tonometer and non contact tonometer (NCT). This study aims to determine difference of IOP level measured by schiotz tonometer and non contact tonometer. Methods: This study was an observational analytic research with cross sectional approach. This study was conducted on November 2015 at Solo Eye Center Surakarta. The sample was collected by using consecutive sampling. Subjects were patient aged >20 years old. Dependent variable was IOP. Independent variable were schiotz tonometer results and NCT results. Data was collected by IOP measurement with both tonometers. The analysis technique used in this study were Mann Whitney and Kappa test . Results: The mean age of subjects was 31.84 17.05(mean SD) years. This study showed a mean of the difference of IOP level between schiotz tonometer and NCT, with p value was p=0.002 for IOP measurement of right eye and p<0.001 for IOP measurement of left eye. The mean of IOP levels as taken by schiotz tonometer were 16.95 3.64 (mean SD) and 19.68 5.34. The mean of IOP levels as taken by NCT were 12.95 3.04 and 13.08 2.52. Kappa test showed a less than chance agreement result between the two tonometers (? = -0.050). Conclusions: There was a significant difference between IOP level measured by schiotz tonometer and non contact tonometer. Keywords: intraocular pressure, schiotz tonometer, non contact tonometer